A six-strut model for nonlinear dynamic analysis of steel infilled frames - Chrysostomou, Christis; Gergely, P; Abel, J.F. (My University, 2002)
A two-dimensional computational model for infill walls is presented. The behavior of an infill wall is prescribed by a strength envelope and a hysteretic loop equation which provide smooth continuous curves. The infill is idealized with six compression-only inclined struts, which follow the behavior defined by the strength envelope and hysteretic loop equations. Three parallel struts are used in each direction, and the off-diagonal struts are located to represent the interaction between the infill and confining steel frame at locations along the beam-column spans where plastic hinges have been observed to form. The advantages of this analytical model are the following: (a) both strength and stiffness degradation of infill walls are modeled; (b) the parameters of the model have physical meaning and can be readily adapted to fit experimental data; (c) the off-diagonal struts allow modeling of the interaction between the infill and the bounding frame; and (d) local behavior, such as the effects of openings, lack of fit, and interface conditions, can be modeled.
Keywords: Infill model; infill wall; macro model; nonlinear mechanics; infill parameters; strength envelope; hysteresis loops